Сайт журнала как инструмент маркетинга знаний - Ильяшенко, Сергей Николаевич (Сумський державний університет, 2014)
В статье изложены результаты анализа эффективности использования сайта научного журнала как инструмента маркетинга знаний, в частности, его коммуникационной политики в среде интернета. Разработаны рекомендации по совершенствованию системы продвижения научных знаний с помощью сайта журнала.

World economy since 2005 has moved to descending wave of a long economic cycle and productions of technological order V (which currently dominates) are gradually losing their relevance, and of the VI one are mainly at the stage of scientific research and development. In these conditions the production and application of new knowledge (scientific, technical, professional) has a chance to enter the path of innovation growth in the mainstream of the innovation development concept. Promotion and popularization of scientific knowledge is provided by scientific journals, especially scientific periodical journals, which are the basis of technical and professional knowledge on the one hand, and generalize and systematize the available technical and vocational achievements on the other hand. Scientific and applied developments which are published there can be the basis for further research, they can also be implemented in practical activities of business structures, government, regional and local government. Website in the Internet is an effective and instantaneous tool for expanding the audience of the scientific journal, which allows enter the foreign countries, with minimal cost and still provide the individualization of communication with readers. It is not only the tool to promote scientific knowledge of certain subjects, but it can also be used to gather information about its target audience. The aim of this study is to analyze the efficiency of the site scientific journal as a marketing tool in the sphere of Internet knowledge and to give recommendations for improving the system of scientific knowledge advancing.
Journal site as the tool of knowledge marketing
Keywords: коммуникационная политика; продвижение знаний; научные журналы; WEB-аналитика; характеристика посещений сайта; основные источники трафика; knowledge marketing; communication policy; promotion of knowledge; scientific journal; magazine website; WEB-analytics